PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MASKER MEDIS SENSI PADA MAHASISWA UNIVERSITAS TEKNOLOGI SUMBAWA: Indonesia - Sumayah Nur Rohmah jmb; Serli Oktapiani (Journal of Management and Business, 2021)
This study aimed to examine the influence of price and product quality on purchasing decisions for Sensi Medical Masks at Sumbawa University of Technology students. The variables used were Price, Product Quality and Purchasing Decision. The method used was quantitative research method through causal associative approach. This research will determine the significant relation between the variables studied. The population was all active students of the Sumbawa Technology University with a purposive sampling technique comprising of 100 active students who have purchased and used Sensi medical masks within the last 6 months. The instrument used was a questionnaire and the analytical tool used was SPSS. The type of data was primary data obtained from the results of filling out a questionnaire with a 4-point Likert scale assessment. The analytical technique used was multiple linear regression analysis. The results of this study indicated that the variables of Price and Product Quality have a significant positive influence on purchasing decisions for Sensi medical masks at Sumbawa University of Technology students, as evidenced by the results of the t-test calculation (partial) where the significance value of the Price variable was 0.041 < 0.05 with a value of tcount 2,087 > a value ttable 1,984 and Product Quality variable of 0,000 < 0,05 with a value of tcount 6,451 > a value of ttable 1,984.